Answer:
The base is x^4 -2x^3 -3x-1
Step-by-step explanation:
We know the perimeter of a triangle is the sum of the three sides
P = s1+s2+s3
We know the perimeter is 5 x^4 − 2 x^3 + x − 3
and two of the legs are 2 x^4 + 2 x − 1 since it is an isosceles triangle
P = 2s1 + s3
Subtract 2s1 from each side
P-2s1 =2s1 +s3 -2S1
P -2s1 =s3
Substituting what we know
5 x^4 − 2 x^3 + x − 3 - 2(2 x^4 + 2 x − 1) = s3
Distribute the -2
5 x^4 − 2 x^3 + x − 3 - 4 x^4 -4 x + 2 = s3
Combine like terms
5 x^4-4x^4 − 2 x^3 + x -4 x -3+ 2 = s3
x^4 -2x^3 -3x-1 =s3
The base is x^4 -2x^3 -3x-1